#TITLE_ALTERNATIVE# - FATIRAHMAN (NIM 10204066); Pembimbing: Dr. Yudi Darma dan Dr. Rizal Kurniadi, TRI
The performance of Si/Ge/Si quantum dot based floating gate MOS memory including its retention characteristic and programming operation speed has been simulated. The simulation results show the retention characteristic improvement with value up to 109 s or around 10 years while the programming time that involving writing and erasing time is at the order of ms. This good retention characteristic is influenced by the embedded Ge nanocrystal in the Si dot that promote compound potential well inside the dot due to its narrower band gap rather than that of Si. Moreover, cladding Ge by Si nanocrystal allows us to keep the good Si-SiO2 interface instead of poor Ge-Oxide interface. This Si/Ge/Si quantum dot memory is a promising candidate as superb nanostructure based memory devices.